Chemical properties of different rattan species traded in Central Sulawesi Province - ANDI TANRA TELLU (Society for Indonesian Biodiversity, 2008)
The aim of this study was to undstand chemical properties of different rattan species traded in Central Sulawesi Province. The chemical of rattan were tested according to SII.1657-85 for wich character of holoselulosa, SII.0443-81 for wich character of ï¡-selulosa, SII.0528-81 for wich character of lignin, and SII.1292.85 for wich character of silica. The study indicated that chemical properties of rattan varied amongst the species. The differences are supposed to have important criteria in identifying different species of rattan species traded in Central Sulawesi. Based on the result the highest quality of rattan is Calamus inops and the lowest is Calamus ornatus var. celebicus (lambang).Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: chemical, rattan, traded.